Comparison of threshold hydrologic response across northern catchments. Issue 16 (10th June 2015) - Ali, Genevieve; Tetzlaff, Doerthe; McDonnell, Jeffrey J.; Soulsby, Chris; Carey, Sean; Laudon, Hjalmar; McGuire, Kevin; Buttle, Jim; Seibert, Jan; Shanley, Jamie; Bishop, Kevin; Seibert, Jan
Abstract Nine mid‐latitude to high‐latitude headwater catchments – part of the Northern Watershed Ecosystem Response to Climate Change (North‐Watch) programme – were used to analyze threshold response to rainfall and snowmelt‐driven events and link the different responses to the catchment characteristics of the nine sites. The North‐Watch data include daily time‐series of various lengths of multiple variables such as air temperature, precipitation and discharge. Rainfall and meltwater inputs were differentiated using a degree‐day snowmelt approach. Distinct hydrological events were identified, and precipitation‐runoff response curves were visually assessed. Results showed that eight of nine catchments showed runoff initiation thresholds and effective precipitation input thresholds. For rainfall‐triggered events, catchment hydroclimatic and physical characteristics (e.g. mean annual air temperature, median flow path distance to the stream, median sub‐catchment area) were strong predictors of threshold strength. For snowmelt‐driven events, however, thresholds and the factors controlling precipitation‐runoff response were difficult to identify. The variability in catchments responses to snowmelt was not fully explained by runoff initiation thresholds and input magnitude thresholds. The quantification of input intensity thresholds (e.g. snow melting and permafrost thawing rates) is likely required for an adequate characterization of nonlinear spring runoff generation in such northern environments. Copyright © 2014 John Wiley & Sons, Ltd.